2017
DOI: 10.1038/s41598-017-12421-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes and canonical pathways in the ascending thoracic aortic aneurysm – The Tampere Vascular Study

Abstract: Ascending thoracic aortic aneurysm (ATAA) is a multifactorial disease with a strong inflammatory component. Surgery is often required to prevent aortic rupture and dissection. We performed gene expression analysis (Illumina HumanHT-12 version 3 Expression BeadChip) for 32 samples from ATAA (26 without/6 with dissection), and 28 left internal thoracic arteries (controls) collected in Tampere Vascular study. We compared expression profiles and conducted pathway analysis using Ingenuity Pathway Analysis (IPA) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…We and others [16,17] recently confirmed that molecular pathways related to calcification dominate in end-stage carotid plaques. While osteolytic processes, suggesting reduced calcification, were prevalent in plaques from symptomatic patients, plaques from patients on statin therapy and asymptomatic ones were enriched in processes associated with increased calcification [8].…”
Section: Introductionsupporting
confidence: 59%
“…We and others [16,17] recently confirmed that molecular pathways related to calcification dominate in end-stage carotid plaques. While osteolytic processes, suggesting reduced calcification, were prevalent in plaques from symptomatic patients, plaques from patients on statin therapy and asymptomatic ones were enriched in processes associated with increased calcification [8].…”
Section: Introductionsupporting
confidence: 59%
“…For IPA analyses, we used two scores: an ‘enrichment’ score (Fisher’s exact test P -value) that measures the overlap of observed and predicted regulated gene sets, and a Z-score that assesses the match of observed and predicted upregulation/downregulation patterns [ 21 ]. The inclusion criteria for genes selected for the analysis was a fold change > ± .8 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, pathway analysis uncovered novel axonal guidance genes that were distinctly elevated in TAA. In a recently published study, this pathway was also detected in a larger cohort of patients suffering from TAA although the authors did not focus their analysis on these axonal cues [19]. Notably, two of the most essential families of genes in the axon guidance pathway, Netrins and Semaphorins were increased in TAA aortic tissue suggesting they could have a causative role in the degenerative mechanisms in TAA development.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA Sequencing analysis, we used histologically non-diseased and non-atherosclerotic ITAs as controls because due to logistic reasons we did not yet have access to non-diseased cadaver aortic tissues. ITAs share similar features with aorta and have also been used in previous studies as control samples for ascending and descending TAA [19,48]. Notably, both ITA and TAA samples were processed and analyzed within same experimental settings to avoid methodological artefacts.…”
Section: Limitations Of the Studymentioning
confidence: 99%